2019
DOI: 10.1101/543256
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

RapidAIM: A culture- and metaproteomics-based Rapid Assay of Individual Microbiome responses to drugs

Abstract: 13Background: Human-targeted drugs may exert off-target effects on the gut microbiota. 14 However, our understanding of such effects is limited due to a lack of rapid and scalable assay to 15 comprehensively assess microbiome responses to drugs. Drugs can drastically change the overall 16 microbiome abundance, microbial composition and functions of a gut microbiome. Although we 17 could comprehensively observe these microbiome responses using a series of tests, for the 18 purpose of a drug screening, it is … Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
26
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
4
3

Relationship

4
3

Authors

Journals

citations
Cited by 14 publications
(27 citation statements)
references
References 72 publications
1
26
0
Order By: Relevance
“…There are numerous types of marketed RS products, which are derived from various plant sources and are processed in to RS in different ways. Our study suggested the importance of individualized screening of dietary RS, using high-throughput approaches like RapidAIM assay [42], for improving health or for their utilization as personalized intervention for human diseases. shift the in vitro gut microbiome [22,23], was used as the positive control.…”
Section: Discussionmentioning
confidence: 98%
“…There are numerous types of marketed RS products, which are derived from various plant sources and are processed in to RS in different ways. Our study suggested the importance of individualized screening of dietary RS, using high-throughput approaches like RapidAIM assay [42], for improving health or for their utilization as personalized intervention for human diseases. shift the in vitro gut microbiome [22,23], was used as the positive control.…”
Section: Discussionmentioning
confidence: 98%
“…Fecal inocula were thawed at 37°C and inoculated at a concentration of 2% (w/v) into a 96-well deep-well plate containing 1 mL MiPro optimized sterile and pre-reduced culture medium (2.0 g L 1 peptone water, 2.0 gL -1 yeast extract, 0.5 g L -1 L-cysteine hydrochloride, 2 mL L -1 Tween 80, 5 mg L -1 hemin, 10 ÎŒL L -1 vitamin K1, 1.0 g L -1 NaCl, 0.4 g L -1 K 2 HPO 4 , 0.4 g L -1 KH 2 PO 4 , 0.1 g L -1 MgSO 4 ·7H 2 O, 0.1 g L -1 CaCl 2 ·2H 2 O, 4.0 g L -1 NaHCO 3 , 4.0 g L -1 porcine gastric mucin, 0.25 g L -1 sodium cholate, and 0.25 g L -1 sodium chenodeoxycholate) as per Li et al . in an anaerobic workstation [20, 21]. BAF and IBAF were added at 2% (v/v) and 5% (v/v) to the media.…”
Section: Methodsmentioning
confidence: 99%
“…We have developed an in vitro microbiome culturing system (MiPro) coupled to a downstream bioinformatics toolbox collectively called RapidAIM (or rapid assay of an individual microbiome) that measures compositional and functional changes in the gut microbiome in response to dietary and therapeutic interventions [20, 21]. RapidAIM can measure the impact of products on the microbiota and can be used to stratify people in clinical studies.…”
Section: Introductionmentioning
confidence: 99%
“…This resulted in 5946 differential features for further analysis. Signi cant features were subjected to clustering and correlation by MetaboAnalyst 4.0 [69][70][71][72].…”
Section: Metabolomementioning
confidence: 99%